Implementation of Community Empowerment Through the PSBI Bank Indonesia CSR Program - Ilianti, Febby; Atmadja, I Ketut; Yulianingsih, Wiwin (Universitas Negeri Semarang, 2024)
Community empowerment is an effort to enhance the dignity and honor of a segment of our society trapped in poverty and backwardness. PSBI is a Corporate Social Responsibility (CSR) program provided by Bank Indonesia as a form of empowerment for the community. Objective: This study aims to analyze the PSBI programs in empowering various sectors within the community. Method: This research employs a literature review method concerning companies with CSR programs for community empowerment, specifically focusing on Bank Indonesia. Results: The study shows that community empowerment conducted by Bank Indonesia through the PSBI CSR program applies the “ACTORS” theory. In this theory, Bank Indonesia provides freedom, trust, supervision, and full support to the community to propose and manage their programs, aiming to create a greater impact on the surrounding community's lives. Conclusion: The PSBI program by Bank Indonesia successfully impacts community empowerment through the “ACTORS” theory-based approach. The support given by Bank Indonesia enables the community to become more independent and capable of developing local potential. Novelty: This study contributes new insights by highlighting the implementation of the “ACTORS” theory in the PSBI CSR program of Bank Indonesia, a topic that has not been extensively covered in the literature on community empowerment through CSR..